Hybrid strontium bromide-natural graphite composites for low to medium temperature thermochemical energy storage: Formulation, fabrication and performance investigation. (15th June 2018) - Cammarata, A.; Verda, V.; Sciacovelli, A.; Ding, Y.
Graphical abstract: Highlights: A composite thermochemical storage material was proposed and studied. The material is a promising candidate for thermal storage applications up to 150 °C. Increase in thermal conductivity and energy storage density were demonstrated. Links between material structure and thermo-physical property were demonstrated. Abstract: Thermochemical energy storage has the potential to provide efficient, compact and long duration storage of thermal energy. Major advancements, however, are needed for such a technology to meet performance and cost targets. Here we present a study on novel composites for low to medium temperature thermochemical energy storage (<150 °C) with an aim to maximize energy density and to understand the associated mass and heat transport phenomena. The composites were made of strontium bromide hexahydrate and natural graphite with the latter acting as a supporting matrix. We used a simple manufacturing method to fabricate the composites and experimentally characterized the performance of the materials using various methods including thermogravimetry, laser flash analysis and dynamic vapor sorption. The results showed that the composites achieved an energy density above 600 kJ/kg with the storage process occurring mostly below ∼100 °C – a promising feature for domestic applications. The results also showed that the natural graphite could improve the hydration-dehydration kinetics by reducing hysteresis and a fourfold increase in the thermal conductivity could be achieved with 20% of natural graphite in the composite.